Characterization of the melanocortin-4-receptor nonsense mutation W16X in vitro and in vivo - Bolze, F; Rink, N; Brumm, H; Kühn, R; Mocek, S; Schwarz, A-E; Kless, C; Biebermann, H; Wurst, W; Rozman, J; Klingenspor, M (The pharmacogenomics journal, 2013)
Several genetic diseases are triggered by nonsense mutations leading to the formation of truncated and defective proteins. Aminoglycosides have the capability to mediate a bypass of stop mutations during translation thus resulting in a rescue of protein expression. So far no attention has been directed to obesity-associated stop mutations as targets for nonsense suppression. Herein, we focus on the characterization of the melanocortin-4-receptor ( MC4R ) nonsense allele W16X identified in obese subjects. Cell culture assays revealed a loss-of-function of Mc4r X16 characterized by impaired surface expression and defect signaling. The aminoglycoside G-418 restored Mc4r X16 function in vitro demonstrating that Mc4r X16 is susceptible to nonsense suppression. For the evaluation of nonsense suppression in vivo , we generated a Mc4r X16 knock-in mouse line by gene targeting. Mc4r X16 knock-in mice developed hyperphagia, impaired glucose tolerance, severe obesity and an increased body length demonstrating that this new mouse model resembles typical characteristics of Mc4r deficiency. In a first therapeutic trial, the aminoglycosides gentamicin and amikacin induced no amelioration of obesity. Further experiments with Mc4r X16 knock-in mice will be instrumental to establish nonsense suppression for Mc4r as an obesity-associated target gene expressed in the central nervous system.